2012
DOI: 10.1044/1092-4388(2011/10-0263)
|View full text |Cite
|
Sign up to set email alerts
|

Nonword Repetition: The Relative Contributions of Phonological Short-Term Memory and Phonological Representations in Children With Language and Reading Impairment

Abstract: Phonological short-term memory and phonological representations both significantly contribute to NWR. The predictive strength of the quality of phonological representations changes during development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 34 publications
4
107
0
3
Order By: Relevance
“…Smith et al, 2014). Consistent with this interpretation, Boada and Pennington (2006) provided evidence that reading-impaired children have less fine-grained phonological representation, linked to poorer performance in pseudoword repetition tasks (see Rispens & Baker, 2012, for further discussion).…”
Section: Pseudoword Repetitionmentioning
confidence: 81%
“…Smith et al, 2014). Consistent with this interpretation, Boada and Pennington (2006) provided evidence that reading-impaired children have less fine-grained phonological representation, linked to poorer performance in pseudoword repetition tasks (see Rispens & Baker, 2012, for further discussion).…”
Section: Pseudoword Repetitionmentioning
confidence: 81%
“…Results have demonstrated that the test is an excellent task not only for measuring phonological memory but also for evaluating children's language development since scores on nonword repetition correlate positively and significantly with other standard measures of language development such as vocabulary level. This is supported by works conducted in English (Gathercole & Baddeley, 1989;Hoff, Core & Bridges, 2008;Roy & Chiat, 2004), Spanish (Mariscal & Gallego, 2013;Rujas, 2014), Dutch (Rispens & Baker, 2012), or Italian (D'Odorico, Assanelli, Franco & Jacob, 2007.…”
Section: Introductionmentioning
confidence: 68%
“…A deficit in either phonological skills or naming speed is thought to result in a less severe form of reading disability than a combined deficit. While tasks such as rhyming, alliteration, categorization, phoneme blending, segmentation, elision, and nonword repetition (NWR) measure phonological skill [33,[36][37][38][39], rapid automatic naming (RAN) is the primary measure of naming speed. There exists some controversy regarding the theoretical explanations for the relationship between naming speed and reading [40], with differing key constructs thought to underly the relationship including phonological awareness [41], orthographic processing [42], and general cognitive processing or executive function [43].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Lower English sentence repetition scores were associated with lower RAN scores, but higher English sentence repetition scores were not significantly related to RAN scores. This finding seems to suggest that the RAN task is a more general cognitive-linguistic processing task and not a domain-specific language task with regard to English morphosyntactic skills for DLLs [19,39]. The English sentence repetition task was designed to be an indicator specifically of English grammatical knowledge for DLLs [66].…”
Section: Relationship To Sentence Imitationmentioning
confidence: 99%
See 1 more Smart Citation